Stylistics Analysis In Literature of Figurative Language Used In Black Lives Matter Community’s Poems - Dedi Efendi (Fakultas Sastra Universitas Ekasakti, 2021)
This research analyzed about figurative language and social values in three poems of Black Live Matter (BLM) community’s poem in America. The purposes of this research are to describe the kinds of figurative language and social values in three poems of BLM community’s poem. In this research, the writer used the descriptive qualitative method and used theory of figurative language by Perrine (1992) and theory of social values by Amir in Sukatman (1991). Data are explained by find the meaning and described them based on the kinds of figurative language through four procedure, they are: identifying, classiying, analyzing and making the conclusion from the data. The result of this research are the writer found about 19 data of figurative language of the poems. Hyperbole is the dominant kind of figurative language in those three poems ,because hyperbole is the appropriate of figurative language for BLM’s proponents for looking for help. Beside, social values also found in these poems, the most dominant social value in these poems is social value of humanity. Humanity is one of the biggest issue for black people in United State of America.